Clonotypic Light Chain Peptides Identified for Monitoring Minimal Residual Disease in Multiple Myeloma without Bone Marrow Aspiration. (6th January 2020) - Bergen, H Robert; Dasari, Surendra; Dispenzieri, Angela; Mills, John R; Ramirez-Alvarado, Marina; Tschumper, Renee C; Jelinek, Diane F; Barnidge, David R; Murray, David L
Abstract: BACKGROUND: Analytically sensitive techniques for measuring minimal residual disease (MRD) in multiple myeloma (MM) currently require invasive and costly bone marrow aspiration. These methods include immunohistochemistry (IHC), flow cytometry, quantitative PCR, and next-generation sequencing. An ideal MM MRD test would be a serum-based test sensitive enough to detect low concentrations of Ig secreted from multifocal lesions. METHODS: Patient serum with abundant M-protein before treatment was separated on a 1-dimensional SDS-PAGE gel, and the Ig light-chain (LC) band was excised, trypsin digested, and analyzed on a Q Exactive mass spectrometer by LC-MS/MS. We used the peptide's abundance and sequence to identify tryptic peptides that mapped to complementary determining regions of Ig LCs. The clonotypic target tryptic peptides were used to monitor MRD in subsequent serum samples with prior affinity enrichment. RESULTS: Sixty-two patients were tested, 20 with no detectable disease by IHC and 42 with no detectable disease by 6-color flow cytometry. A target peptide that could be monitored was identified in 57 patients (91%). Of these 57, detectable disease by LC-MS/MS was found in 52 (91%). CONCLUSIONS: The ability to use LC-MS/MS to measure disease in patients who are negative by bone marrow–based methodologies indicates that a serum-based approach has more analytical sensitivity and may be useful for measuring deeper responses to MM treatment. The method requires no bone marrow aspiration.